2022
DOI: 10.51126/revsalus.v4i1.136
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the inorganic content and the polymerization of the organic matrix of resin composites for dentistry: a narrative review

Abstract: Introduction: In recent years, resin-matrix composite materials have revealed a fast technological improvement for dental applications. However, there are still some drawbacks related to the chemical composition, polymerization, and mechanical properties of resin-matrix composites with consequences in long-term clinical success. Objective: This study aimed to perform a narrative review regarding the effects of inorganic fillers on the organic matrix polymerization of resin-matrix composites. Materials and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…TEGDMA and Bis-EMA. In which Bis-GMA is a high molecular weight di-methacrylate monomer known to influence the mechanical and physical properties of resin material and provide high EM [25]. Previous studies confirmed that, increased filler content has a positive influence on flexure properties [26] and this goes along with present results.…”
Section: Discussionsupporting
confidence: 89%
“…TEGDMA and Bis-EMA. In which Bis-GMA is a high molecular weight di-methacrylate monomer known to influence the mechanical and physical properties of resin material and provide high EM [25]. Previous studies confirmed that, increased filler content has a positive influence on flexure properties [26] and this goes along with present results.…”
Section: Discussionsupporting
confidence: 89%
“…Bis-GMA, one of the monomers in the organic matrix content, provides physical properties such as high molecular mass and high E M [59]. In some available composites today, Bis-EMA can be used instead of Bis-GMA.…”
Section: Discussionmentioning
confidence: 99%
“…Most resin-matrix cements contain high molecular weight monomers (Bis-GMA, UDMA, TEGDMA, and hydroxyl ethyl methacrylate (HEMA), as described in Table 1 [ 46 ]. Bis-GMA has a high molar mass (512 g mol −1 ) and a high viscosity (600–1000 Pa.s −1 ), which limits the addition of inorganic particles to resin-based materials [ 41 , 47 , 48 ]. Additionally, UDMA is commonly used as a base monomer in self-adhesive resin-matrix cements in combination with TEGDMA [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CQ/TA complex is stimulated by visible light at wavelengths ranging from 420 up to 490 nm [ 69 ], although the light absorption peak is recorded at 470 nm ( Table 1 ) [ 52 , 53 ]. Regarding the light-curing reaction, blue visible light (at 470 nm) transmitted by a LCU is absorbed by the CQ/TA complex, involving three fundamental steps: (1) polymeric chain growth without restrictions, in which the monomer concentration and free radicals determine the kinetic reactions; (2) fast viscosity increase with restricted mobility of free radicals and an irreversible increase in the elastic modulus of the resin matrix (gel point); and (3) vitrification and end of the reaction with a high viscosity level [ 41 , 47 , 48 , 70 ]. The increase in viscosity limits the movements of the remaining monomers responsible for additional polymerization [ 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation